Lifestyle and Other Factors Explain One-Half of the Variability in the Serum 25-Hydroxyvitamin D Response to Cholecalciferol Supplementation in Healthy Adults. Issue 11 (28th September 2016) - Rees, Judy R; Mott, Leila A; Barry, Elizabeth L; Baron, John A; Bostick, Roberd M; Figueiredo, Jane C; Bresalier, Robert S; Robertson, Douglas J; Peacock, Janet L
Abstract: Background: Many factors have been associated with serum 25-hydroxyvitamin D [25(OH)D] concentrations in observational studies, with variable consistency. However, less information is available on factors affecting the magnitude of changes in serum 25(OH)D resulting from vitamin D supplementation. Objective: This study aimed to identify factors associated with the serum 25(OH)D response to supplementation with 1000 IU cholecalciferol/d during the first year of a large, multicenter, randomized, placebo-controlled colorectal adenoma chemoprevention trial. Methods: Eligible older adults who were not vitamin D–deficient [serum 25(OH)D ≥12 ng/mL] were randomly assigned in a modified 2 × 2 factorial design to 1 of 4 groups: daily 1000 IU cholecalciferol, 1200 mg Ca as carbonate, both, or placebo. Women could elect 2-group (calcium ± cholecalciferol) random assignment. In secondary analyses, we used multivariable models to assess factors associated with serum 25(OH)D concentrations in all enrollees ( n = 2753) and with relative changes in serum 25(OH)D after 1 y cholecalciferol supplementation among those randomly assigned ( n = 2187). Results: In multivariable models, 8 factors accounted for 50% of the variability of proportional change in serum 25(OH)D after cholecalciferol supplementation. Larger increases were associated with being female (34.5% compared with 20.5%; P < 0.001) and with lower baseline serum 25(OH)D ( P < 0.0001), optimal adherence to study pill intake ( P = 0.0002), wearing long pants and sleeves during sun exposure ( P = 0.0002), moderate activity level ( P = 0.01), use of extra vitamin D–containing supplements during the trial ( P = 0.03), and seasons of blood draw ( P ≤ 0.002). Several genetic polymorphisms were associated with baseline serum 25(OH)D and/or serum response, but these did not substantially increase the models' R 2 values. Other factors, including body mass index, were associated with serum 25(OH)D at baseline but not with its response to supplemental cholecalciferol. Conclusions: The factors that most affected changes in serum 25(OH)D concentrations in response to cholecalciferol supplementation included sex, baseline serum 25(OH)D, supplement intake adherence, skin-covering clothes, physical activity, and season. Genetic factors did not play a major role. This trial was registered at www.clinicaltrials.gov as NCT00153816.